Impact of free-trade initiatives on the Caribbean Basin : from democracy to efficiency in Belize (1998)
Explores the intertwined meanings attributed to development and democracy by US government discourse in the 1980s, their relation to U.S. policies and their impact on small, dependent nations in the Caribbean, taking Belize as an example. Examines how Belizeans receive these ideas, negotiated local meanings for them and put them to use in constructing social alliances that could shape policies. Focuses on recent shifts in U.S. emphasis from democracy to efficiency and the implications of this shift for Belize in particular and the Caribbean more generally.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT